The importance of Internet of Things (IoT) applications in advancing teaching and learning in property management practices - Rosman, Siti Hasniza; Ismail, Suhana; Ab Majid, Rohayu; Ahmad Zawawi, Emma Marinie (Penerbit UiTM (UiTM Press), 2026)
The integration of the Internet of Things (IoT) into property management is reshaping professional practices and transforming how future practitioners are taught and trained. This study examines the importance of IoT applications in advancing teaching and learning within property management education. The research objectives are to identify key IoT attributes, evaluate their relevance to property management pedagogy, and analyse how these attributes can be embedded into teaching strategies and learning outcomes. A mixed-methods approach was employed, involving a literature review, semi-structured interviews with three industry professionals, and an online survey of 306 respondents. The findings highlight that IoT attributes such as reducing carbon emissions, improving work productivity, enhancing tenant– management relationships, strengthening safety and security, and ensuring effective indoor air quality management are not only significant in professional practice but also serve as valuable content for teaching and curriculum design. Furthermore, attributes such as space utilisation analytics, cloud- based maintenance, real-time communication, and technological innovation showed medium to strong correlations with property management practices (r = 0.482), underscoring their pedagogical relevance. These findings suggest that integrating IoT concepts into property management teaching enhances students’ digital literacy, practical understanding, and readiness for industry transformation. Overall, the study helps bridge the gap between industry innovation and higher education by demonstrating how IoT can be leveraged to enrich teaching and learning in property management.